2005
DOI: 10.1111/j.1365-2443.2005.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel isoform of Vinexin, Vinexin γ, regulates Sox9 gene expression through activation of MAPK cascade in mouse fetal gonad

Abstract: Recent loss-of-function and gain-of-function studies have revealed that transcription factor Sox9 is required for testis formation by governing Sertoli cell differentiation, and thereafter regulating transcription of Sertoli marker genes. In the present study, we identified a novel isoform of Vinexin, which is expressed in somatic cells but not germ cells of sexually indifferent stages of fetal gonads. After the sex is determined, the expression continues in testicular Sertoli cells. Immunohistochemical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 67 publications
(74 reference statements)
2
55
0
Order By: Relevance
“…The ouchless mutation affects the expression of sorbs3, a scaffold protein known to interact with components of focal adhesions, as well as with effectors of ErbB signaling, including Sos, Raf and ERK (Kioka et al, 1999;Akamatsu et al, 1999;Mitsushima et al, 2004;Matsuyama et al, 2005;Mitsushima et al, 2007;Gehmlich et al, 2007). Our experiments support the hypothesis that Sorbs3 and ErbB2/3 are part of the same genetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The ouchless mutation affects the expression of sorbs3, a scaffold protein known to interact with components of focal adhesions, as well as with effectors of ErbB signaling, including Sos, Raf and ERK (Kioka et al, 1999;Akamatsu et al, 1999;Mitsushima et al, 2004;Matsuyama et al, 2005;Mitsushima et al, 2007;Gehmlich et al, 2007). Our experiments support the hypothesis that Sorbs3 and ErbB2/3 are part of the same genetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Vinexinb is reported to bind with a Ras-guanine nucleotide-exchange factor (Ras-GEF) mSos and regulate the epidermal growth factor (EGF)-induced activation of c-jun N-terminal kinase (JNK) (Akamatsu et al, 1999). Vinexinb also interacts with activated version of extracellular signal-regulated kinase (ERK) and c-Raf, an upstream activator of ERK (Suwa et al, 2002;Mitsushima et al, 2004;Matsuyama et al, 2005). While the third SH3 domain interacts with mSos and is essential for EGF-mediated JNK activation (Akamatsu et al, 1999), a linker region between second and third SH3 domains is required for anchorage-dependent activation of ERK2 induced by EGF (Suwa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular architecture of this family is highly conserved; they share a N-terminally located sorbinhomology (SoHo) domain and three src-homology 3 (SH3) domains in the C-terminal region. Vinexin is transcribed into several alternative forms including vinexina, b and g (Kioka et al, 1999;Matsuyama et al, 2005). While vinexina and g are larger variants and have a SoHo domain, vinexinb is a short form containing only three SH3 domains.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that Wnt4 and the fibroblast growth factor 9 gene (Fgf9), which both work downstream of SRY, antagonize each other to control Sox9 expression [41]. Pathways induced by mitogen-activated protein kinase (MAPK) [42,43], RHO-ROCK [44] and vinexin γ-MAPK have been shown to regulate Sox9 expression both in cell culture and in vivo [45]. SOX9 nuclear translocation was also shown to be regulated via importin β1 [46] and calmodulin [47], which further indicates that SRY and/or SOX9 are regulated at the post-translational level.…”
Section: Is It All About the Y Chromosome?mentioning
confidence: 99%